Perceived barriers to the use of Traditional Chinese Medicine (TCM): A systematic literature review. - Lock, Rou Fen; Chen, I-Chi; Gengeswari, K; Te, Kian Keong (International Journal of Accounting, Finance and Business, 2025)
Barriers towards the utilization of Traditional Chinese Medicine (TCM) have significant impacts such as increased difficulty in integrating into mainstream healthcare and restricting the choice for the public to choose alternative option for overall well-being. Understanding the barriers can help the policymakers and healthcare professionals carry out implementation to increase treatment utilization. Hence, this paper aims to identify the perceived barriers regarding TCM utilization. Six databases, including Scopus, PubMed, Emerald Insights, Semantic Scholar, ScienceDirect, and Google Scholar, were used in the review, producing one hundred and sixty-eight studies. Also, there are thirteen studies identified through backward citation searching. Fourteen studies were selected based on the PRISMA guideline. The selected studies were reviewed based on the type of literature. Through the review, the common barriers identified include cost, knowledge, side-effects of the treatment, and healthcare professionals. In addition, the review also discovered that there are several demographic profiles that influence barriers, including age, employment, education, race, income, geographical location, marital status, and ethnicities.